The Influence of Social Values and Childhood Socialization on Occupational Gender Segregation and Wage Disparity. - Kalantari, Behrooz (Public Personnel Management)
This work investigates continued and persistent wage disparity between women and men in the U.S. labor market and seeks to identify the main cause of this phenomenon. Statistics are provided to demonstrate that although female participation in the paid workforce has increased, overall women's wages relative to men's has not. Using the latest statistics, this study argues that occupational gender segregation is a fact in the job market and one of the major causes of wage disparity between two genders. The author contends that job segregation itself is a by product of social values and especially the early socialization of children in society. This work explores how social values influence and formulate the content and process of socialization in children's early education. The childhood socialization phenomenon, including its significance, origin and primary agents, as well as its relationship with job segregation, is examined in depth. In conclusion, this study advocates policy changes in order to achieve a non-gender based wage system in the labor market. It argues that wage fairness is achievable in the long-term through careful planning.